Factors influencing concurrent wasting, stunting, and underweight among children under five who suffered from severe acute malnutrition in low- and middle-income countries: a systematic review - Dassie, Godana Arero; Chala Fantaye, Tesfaye; Charkos, Tesfaye Getachew; Sento Erba, Midhakso; Balcha Tolosa, Fufa (Frontiers in Nutrition, 2024)
Background: Wasting, stunting, and underweight in children are complex health challenges shaped by a combination of immediate, underlying, and systemic factors. Even though there is a lot of data demonstrating that the causation routes for stunting and wasting are similar, little is known about the correlations between the diseases in low- and middle-income nations. Objective: The objective is to evaluate the factors that concurrently affect wasting, stunting, and underweight in <5-year-olds with SAM.Method: This review adhered to the PRISMA guidelines. We searched every electronic database that was available, from the medRxiv pre-print site, PubMed, MEDLINE, EMBASE, Cochrane Library, Web of Science, PsycINFO, CINAHL, Google Scholar, and Scopus, in addition to the Science Direct search engine. We took research conducted in low- and middle-income nations on < 5 yr with SAM. The Newcastle Ottawa Scale was used to assess the studies' quality. Results: After screening and selecting 12 eligible studies, 1,434,207 records were included for analysis. The prevalence of factors influencing concurrent wasting, stunting, and being underweight was 26.42% LMI. Being male sex, the prevalence was higher counter sex, of which wasting, stunting, and underweight were (14.2%), (4.1%), and (27.6%), respectively.Unprotected drinking water was associated with stunting (odds ratio = 0.68; 95CI (0.50, 0.92).Being male (aOR = 2.04, 95% CI: 1.13, 3.68). Lack of prenatal care follow-up was associated with a lower risk of wasting (OR = 2.20, 95% CI: 1.04, 4.64), while low birth weight (<2.5 kg), diarrhea, a younger child, and underweight, wasting, stunting, and underweight were significantly associated with a poor household's: wasting (aOR = 1.71, 95% CI: (0.189, 0.985); BMI-for-age aOR = 2.11, 95% CI: (0.07, 0.895); maternal education: stunting (aOR = 1.52, 95% CI: (0.09, 0.89); underweight (aOR = 1.97, 95% CI: (0.01, 0.73); and open defecation, stunting (aOR = 1.62, 95% CI: (0.06, 0.32); underweight (aOR = 1.92, 95% CI: (0.042, 0.257).Underweight increased with birth order (second born, aOR=1.92, 95% CI 1.09 to 3.36; third born, aOR=6.77, 95% CI 2.00 to 22.82).Conclusion: inadequate dietary intake, illness, food insecurity, poor maternal & child care, poor hygiene and sanitation, & healthcare inaccessibility.